Ultrastructural Observations Reveal the Presence of Channels between Cork Cells - Teixeira, Rita Teresa; Pereira, Helena (MICROSCOPY AND MICROANALYSIS, 2009)
The ultrastructure of phellem cells of Quercus Silber L. (cork oak) and Calotropis procera (Ait) R. Br. were analyzed using electron transmission microscopy to determine the presence or absence of plasmodesmata (PD). Different types of Q. Silber cork samples were studied: one year shoots; virgin cork (first periderm), reproduction cork (traumatic periderm), and wet cork. The channel structures of PD were found in all the samples crossing adjacent cell walls through the suberin layer of the secondary wait. Calotropis phellem also showed PD crossing the cell walls of adjacent cells but in fewer numbers compared to Q. suber. In one year stems of cork oak, it was possible to follow the physiologically active PD with ribosomic accumulation next to the aperture of the channel seen in the phellogen cells to the completely obstructed channels in the dead cells that characterize the phellem tissue.
The following values have no corresponding Zotero field: pub-location: 32 AVENUE OF THE AMERICAS, NEW YORK, NY 10013-2473 USA publisher: CAMBRIDGE UNIV PRESS
Keywords: Calotropis procera; Cork; phellogen; plasmodesmata; Quercus suber; suberin

Ultrastructural Observations Reveal the Presence of Channels between Cork Cells (MICROSCOPY AND MICROANALYSIS, 2009)
The ultrastructure of phellem cells of Quercus Silber L. (cork oak) and Calotropis procera (Ait) R. Br. were analyzed using electron transmission microscopy to determine the presence or absence of plasmodesmata (PD). Different types of Q. Silber cork samples were studied: one year shoots; virgin cork (first periderm), reproduction cork (traumatic periderm), and wet cork. The channel structures of PD were found in all the samples crossing adjacent cell walls through the suberin layer of the secondary wait. Calotropis phellem also showed PD crossing the cell walls of adjacent cells but in fewer numbers compared to Q. suber. In one year stems of cork oak, it was possible to follow the physiologically active PD with ribosomic accumulation next to the aperture of the channel seen in the phellogen cells to the completely obstructed channels in the dead cells that characterize the phellem tissue.